Features of the immunotropic effects of partial components of the balneotherapeutic complex of SPA Truskavets’ - Popovych, Andriy I. (Journal of Education, Health and Sport, 2018)
Background. The arsenal of therapeutic factors of the spa Truskavets’ is not limited to bioactive water Naftussya, but also includes ozokerite applications and mineral baths. The purpose of this study is to quantify the partial immunotropic effects of these balneofactors and also the organic substances and microbiota of Naftussya water. Material and methods. The object of observation were 41 men and 10 women aged 24-70 years old, who came to the spa Truskavets’ for the treatment of chronic pyelonephritis combined with cholecystitis in remission. Immune status evaluated on a set of I and II levels recommended by the WHO. The survey was conducted twice, before and after 7-10-days balneotherapy. 23 patients drinked bioactive water Naftussya (BAWN) by 3,2 mL/kg for 1 hour before meals three times a day, while 7 others volunteers drinked Ozokerite extract by 2 mL dissolved in sweet water (2,5-2,6 mL/kg) one time daily. 8 patients in the third group received BAWN and baths with mineral water (Cl--SO42--Na+-Mg2+ containing salt concentration 25 g/L) and for the other 13 patients in the balneotherapeutic complex included additionally application of Ozokerite on the lumbar region. Results. The most pronounced as stimulating (blood level of total, active and cytolytic T-lymphocytes, Circulating Immune Complexes, IgA and Microbial Count for Staph. aureus) and suppressor (blood level of helper T-lymphocytes and Neutrophils, theirs Killing Index and Bactericydity vs both Staph. aureus and E. coli) action are the organic substances of Ozokerite that contact the surface of the skin, whereas their contact with the mucous of the digestive tract causes less pronounced immunotropic effect. Naftussya water has a stronger effect than the water solution of Ozokerite, apparently due to the additional effects of microbes and organic matter produced by them. In contrast, the bath factors affect the immune parameters of the opposite influences. Microbiota has the most pronounced enhancing effects on the Phagocytose Index of Neutrophils vs. Staph. aureus and blood level of Natural Killers as well as Entropy of Leukocytogram. Instead, organic substances of Ozokerite have the same tangible but opposite effects on these parameters.